A HJT special packaging film and its preparation method and application
By using functional additives to form a cross-linked mesh structure with matrix resin in the packaging film of HJT batteries, the problem of decreasing adhesion force in the HJT battery packaging film in the prior art is solved, high bond strength and excellent aging resistance are achieved, and the service life of the photovoltaic module is extended and the attenuation rate of the photovoltaic efficiency is reduced.
Patent Information
- Application Number
- CN202111553466.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-17
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2041-12-17
AI Technical Summary
The adhesive force of the packaging film of existing HJT batteries decreases in high temperature and high humidity environments, and problems such as delamination and yellowing are prone to occur, which affects the long service life and conversion efficiency of photovoltaic modules.
Acrylate polymer containing functional groups is used as a functional additive to form a crosslinked network structure with the matrix resin through crosslinking reaction, enhancing the reaction capacity with the ITO layer on the surface of the HJT battery, forming stable hydrogen bonds and covalent bonds, and improving bond strength and aging resistance.
It significantly improves the bonding strength between the HJT cell and the packaging film, enhances the tolerance to ultraviolet and humidity, extends the service life of photovoltaic modules and reduces the attenuation rate of the photoconversion efficiency.
Smart Images

Figure BDA0003418433200000081 
Figure BDA0003418433200000091 
Figure BDA0003418433200000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a HJT special packaging adhesive film and a preparation method and application thereof. Background Art
[0002] With the rapid development of photovoltaic technology, the conversion efficiency of crystalline silicon solar cells has increased year by year. In the current photovoltaic industry, the conversion efficiency of monocrystalline silicon solar cells has reached more than 20%, and the conversion efficiency of polycrystalline silicon solar cells has reached more than 19%. However, the silicon-based solar cells with a conversion efficiency of more than 22% that are mass-produced are only back contact solar cells (IBC) and amorphous silicon / crystalline silicon heterojunction solar cells (HJT) with intrinsic thin layers. Compared with IBC cells, HJT cells have many advantages such as low energy consumption, simple process flow, symmetrical structure, low-temperature manufacturing process, high open circuit voltage, good temperature characteristics, and no LID and PID effects. Because HJT cells have a low temperature coefficient, the efficiency and output power decrease relatively less after the temperature rises. A single HJT cell can generate 8 to 10% more electricity than a conventional crystalline silicon cell in a day. At the same time, due to the symmetrical structure, it can be made into a double-sided HJT cell, which can generate more than 10% more electricity than a single side. The double-sided deposited transparent conductive oxide film (TCO) can not only build a series resistance when collecting current, but also play a role in anti-reflection similar to the silicon nitride layer on crystalline silicon cells, thereby forming a higher open circuit voltage and improving conversion efficiency. In addition, the highest temperature in the HJT cell manufacturing process is the formation temperature of the amorphous silicon film (200°C), which avoids the high temperature (950°C) of the traditional crystalline silicon cell to form a PN junction. The use of low-temperature technology can reduce energy consumption while also reducing thermal damage to silicon wafers. HJT cells have no LID effect, which is attributed to the fact that the HJT cell substrate is N-type single crystal silicon. HJT cells also have no PID effect, because the TCO film is deposited on its surface, there is no insulating layer, and there is no chance of surface charge, which structurally avoids the occurrence of PID phenomenon.
[0003] The deposited layer on the surface of HJT batteries is a special inert metal oxide indium tin oxide (ITO), which is highly hydrophobic. For HJT batteries, the selection of packaging materials is crucial, but conventional EVA and POE materials have poor adhesion after packaging. After composite aging, problems such as delamination, yellowing, and a significant decrease in adhesion are prone to occur.
[0004] CN112980340A discloses a packaging film for packaging HJT cells, a preparation method thereof, and a photovoltaic module obtained therefrom. The packaging film for packaging HJT cells disclosed therein comprises an adhesive layer and an EVA layer; the adhesive layer is mainly made of the following components by weight: 100 parts of base resin, 5-10 parts of modified resin, and 1-5 parts of auxiliary agent; the modified resin is mainly made by reacting base resin, initiator, and bonding monomer; the disclosed packaging film introduces a specific modified resin into the adhesive layer, so that the viscosity-increasing mechanism of the packaging film is adapted to the composite ITO anti-reflection light-trapping layer on the surface of HJT, so as to achieve complete bonding between the film and the heterojunction cell, and improve the peeling strength between the film and the HJT cell; at the same time, the EVA layer has a strong peeling strength to the tempered glass or the backplane surface, so as to improve the long-term reliability and service life of the HJT module. However, this method is complex and costly, and the bonding layer and the surface of the HJT battery are simply physically bonded, which can easily lead to risks such as delamination and yellowing in the complex outdoor ultraviolet, high temperature and high humidity environment.
[0005] In summary, it is crucial to develop a HJT-specific encapsulation film that has high bonding strength with HJT cells and excellent resistance to UV and moisture and heat aging. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a HJT-specific packaging film and a preparation method and application thereof, wherein the HJT-specific packaging film is in surface-to-surface contact with the HJT cell, the HJT-specific packaging film has a high bonding strength with the HJT cell, and also has excellent resistance to UV and moisture and heat aging, thereby ensuring a long service life and low light conversion efficiency attenuation rate of photovoltaic modules.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a HJT-specific encapsulation adhesive film, the HJT-specific encapsulation adhesive film comprising a base resin and a functional additive;
[0009] The functional auxiliary agent includes any one or a combination of at least two of acrylic acid ester polymers and derivatives thereof containing functional groups;
[0010] The functional additive participates in the cross-linking reaction, and its molecular chain forms a cross-linked network structure with the matrix resin;
[0011] The functional group includes any one or a combination of at least two of a phosphorus-containing group, an amino group or a carboxyl group, wherein typical but non-limiting combinations include: a combination of a phosphorus-containing group and an amino group, a combination of an amino group and a carboxyl group, a combination of a phosphorus-containing group, an amino group and a carboxyl group, etc.
[0012] The surface of conventional crystalline silicon cells is a silicon nitride structure, which is hydrophilic and has strong adhesion to conventional encapsulation films. It is not easy to delaminate or turn yellow in a long-term high temperature and high humidity environment. The surface structure of HJT cells is ITO. The adhesion between the film and the cell cannot penetrate into the inner part of the serrated deposition layer. It is basically a point-line contact with the grid lines on the surface of the cell. This bonding state is prone to a sharp drop in adhesion under outdoor ultraviolet light and high temperature and high humidity environments. The encapsulation adhesive film provided by the present invention is added with a functional auxiliary agent, wherein the functional group of the functional auxiliary agent includes any one or a combination of at least two of a phosphorus-containing group, an amino group or a carboxyl group, and the functional group is an active group, so that the encapsulation adhesive film can react with the ITO layer on the surface of the HJT battery to form stable structures such as hydrogen bonds and covalent bonds. Different from simple mechanical bonding forces and van der Waals forces, these chemical bonds have higher bond energies, can provide long-term and stable bonding forces between the adhesive film and the battery sheet, and improve the bonding strength with the HJT; and also make the encapsulation adhesive have excellent UV resistance and heat and humidity aging resistance, therefore, the photovoltaic module further formed therefrom has a long service life and a low light conversion efficiency attenuation rate.
[0013] In addition, the encapsulation film has excellent wettability and ductility, and can flow to every corner of the HJT battery cell in a very short time during the film lamination process. The film can achieve complete, tight and uniform adhesion with the irregular surface of the battery cell, and is not prone to delamination, yellowing, decreased adhesion and other abnormalities in complex environments.
[0014] Preferably, the number average molecular weight of the functional additive is 100-5000 g / mol, for example, 500 g / mol, 1000 g / mol, 1500 g / mol, 2000 g / mol, 2500 g / mol, 3000 g / mol, 3500 g / mol, 4000 g / mol, 4500 g / mol, etc.
[0015] The functional additive of the present invention has a number average molecular weight of 100-5000 g / mol, has low viscosity, and has good absorbability with the matrix resin. After mixing and stirring, the particle surface is dry, which can ensure the operability of the production process.
[0016] Preferably, the main chain of the functional auxiliary agent contains at least 2 double bonds, such as 3, 4, 5, etc.
[0017] The functional auxiliary agent of the present invention contains at least two double bonds, and the unsaturated bonds enable the functional auxiliary agent and the matrix resin to form a cross-linked network structure after lamination.
[0018] Preferably, the phosphorus-containing group includes a phosphate substituent and / or a phosphate ester substituent.
[0019] Preferably, when the functional group is a phosphorus-containing group, the functional auxiliary agent includes any one of methacrylate phosphate, dimethyl acrylate phosphate, acrylic acid phosphate, cetostearyl alcohol phosphate or lauryl alcohol ether phosphate, or a combination of at least two of them, wherein typical but non-limiting combinations include: a combination of methacrylate phosphate and dimethyl acrylate phosphate, a combination of dimethyl acrylate phosphate, acrylic acid phosphate and cetostearyl alcohol phosphate, a combination of dimethyl acrylate phosphate, acrylic acid phosphate, cetostearyl alcohol phosphate and lauryl alcohol ether phosphate, etc.
[0020] The present invention prefers the above functional additives because they have low molecular weight and low viscosity and can be directly mixed with other materials and extruded into a film.
[0021] Preferably, the functional additive includes modified oligomers and their derivatives and / or modified oligomers and their derivatives;
[0022] The number average molecular weight of the modified oligomer and its derivatives is 100-1000 g / mol, for example, 200 g / mol, 300 g / mol, 400 g / mol, 500 g / mol, 600 g / mol, 700 g / mol, 800 g / mol, 900 g / mol, etc.;
[0023] The number average molecular weight of the modified oligomer and its derivatives is 1000-5000 g / mol, for example, 1500 g / mol, 2000 g / mol, 2500 g / mol, 3000 g / mol, 3500 g / mol, 4000 g / mol, 4500 g / mol, etc.
[0024] Preferably, when the functional auxiliary agent is a modified oligomer and its derivatives, the functional auxiliary agent includes any one of cetostearyl phosphate, lauryl ether phosphate, acrylic acid phosphate, dimethyl acrylate, tetrahydrofuran acrylate, 2-phenoxyethyl acrylate, methacrylate phosphate, difunctional polyurethane acrylate, 2-hydroxyethyl methacrylate phosphate or alkyl acrylate phosphate, or a combination of at least two of them, wherein typical but non-limiting combinations include: a combination of tetrahydrofuran acrylate and 2-phenoxyethyl acrylate, a combination of methacrylate phosphate, lauryl ether phosphate, difunctional polyurethane acrylate and 2-hydroxyethyl methacrylate phosphate, a combination of methacrylate phosphate, difunctional polyurethane acrylate, acrylic acid phosphate, 2-hydroxyethyl methacrylate phosphate and alkyl acrylate phosphate, and the like.
[0025] The present invention prefers the above functional additives because the modified oligomers have high activity and large molecular weight, and the addition amount and cost can be selectively reduced.
[0026] Preferably, when the functional auxiliary agent is a modified oligomer and its derivatives, the functional auxiliary agent includes any one of di(methacryloyloxyethyl) hydrogen phosphate, multifunctional acrylate phosphate, polyphosphate, phosphazene polyurethane or poly(phosphate-caprolactone-phosphate), or a combination of at least two thereof, wherein typical but non-limiting combinations include: a combination of di(methacryloyloxyethyl) hydrogen phosphate and multifunctional acrylate phosphate, a combination of polyphosphate and phosphazene polyurethane, a combination of di(methacryloyloxyethyl) hydrogen phosphate, multifunctional acrylate phosphate, polyphosphate and phosphazene polyurethane, and the like.
[0027] In the present invention, the multifunctional acrylate phosphate refers to an acrylate phosphate having a functionality of at least 2.
[0028] The present invention prefers the above functional additives because the molecular weight is higher, the chemical bond formed between the adhesive film and the battery cell is more stable, and the bonding density is higher.
[0029] Preferably, the light transmittance of the matrix resin is ≥91%, such as 92%, 93%, etc.
[0030] The reason why the light transmittance of the matrix resin of the present invention is above 91% is that higher light transmittance can improve the power of the component.
[0031] Preferably, the base resin comprises a cross-linkable polyolefin resin.
[0032] Preferably, the matrix resin includes ethylene-vinyl acetate copolymer (EVA resin) and / or POE plastic.
[0033] Preferably, in the ethylene-vinyl acetate copolymer, the mass proportion of vinyl acetate structural units is 28%-33% (for example, 29%, 30%, 31%, 32%, etc.), and the melt index is 3-28g / 10min (for example, 5g / 10min, 10g / 10min, 15g / 10min, 20g / 10min, 25g / 10min, etc.).
[0034] Preferably, the HJT-specific packaging film includes other additives.
[0035] Preferably, the HJT-specific packaging film comprises the following components in parts by weight:
[0036] 100 parts of base resin
[0037] Functional additives 0.1-15 parts
[0038] Other additives 0-8 parts.
[0039] In the present invention, the weight percentage of the base resin is 100 parts.
[0040] The weight proportion of the functional additive is 0.1-15 parts, for example, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, etc., more preferably 0.1-12 parts.
[0041] The weight proportion of other additives is 0-8 parts, for example, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, etc.
[0042] Preferably, the other auxiliary agents include any one of an initiator, a co-crosslinking agent, an ultraviolet light stabilizer, an ultraviolet light absorber, a lubricant or a silane coupling agent, or a combination of at least two thereof, wherein typical but non-limiting combinations include: a combination of an initiator and a co-crosslinking agent, a combination of an ultraviolet light stabilizer, an ultraviolet light absorber and a lubricant, a combination of an initiator, a co-crosslinking agent, an ultraviolet light stabilizer, an ultraviolet light absorber, a lubricant and a silane coupling agent, and the like.
[0043] Preferably, the initiator comprises a peroxide-based initiator.
[0044] Preferably, the initiator includes any one of tert-butyl peroxide-2-ethylhexanoate, dibenzoyl peroxide, di-tert-butyl peroxyisopropylbenzene, 2,5-di-tert-butyl peroxy-2,5-dimethylhexane or tert-amyl peroxide 2-ethylhexyl carbonate, or a combination of at least two thereof, wherein typical but non-limiting combinations include: a combination of tert-butyl peroxide-2-ethylhexanoate and dibenzoyl peroxide, a combination of dibenzoyl peroxide, di-tert-butyl peroxyisopropylbenzene and 2,5-di-tert-butyl peroxy-2,5-dimethylhexane, a combination of dibenzoyl peroxide, di-tert-butyl peroxyisopropylbenzene, 2,5-di-tert-butyl peroxy-2,5-dimethylhexane and tert-amyl peroxide 2-ethylhexyl carbonate, and the like.
[0045] Preferably, the auxiliary cross-linking agent includes any one of 1,6-hexanediol diacrylate, ethoxylated trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, triallyl isocyanurate, triallyl cyanurate, ethoxylated pentaerythritol tetraacrylate, ethylene glycol diacrylate or ethylene glycol dimethacrylate, or a combination of at least two thereof, wherein typical but non-limiting combinations include: a combination of 1,6-hexanediol diacrylate and ethoxylated trimethylolpropane trimethacrylate, a combination of trimethylolpropane trimethacrylate, triallyl isocyanurate and triallyl cyanurate, a combination of ethoxylated trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, triallyl isocyanurate, triallyl cyanurate, ethoxylated pentaerythritol tetraacrylate, ethylene glycol diacrylate or ethylene glycol dimethacrylate, and the like.
[0046] Preferably, the ultraviolet light absorber comprises 2-hydroxy-4-n-octyloxybenzophenone.
[0047] Preferably, the ultraviolet light stabilizer comprises bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0048] Preferably, the lubricant comprises silicone masterbatch.
[0049] Preferably, the silane coupling agent includes any one or a combination of at least two of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane or vinyltri(β-methoxyethoxy)silane, wherein a typical but non-limiting combination includes: γ -A combination of aminopropyltriethoxysilane and γ-aminopropyltrimethoxysilane, a combination of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane, a combination of γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane and vinyltri(β-methoxyethoxy)silane, etc.
[0050] Preferably, the weight proportion of the initiator is 0.2-2 parts, for example, 0.4 parts, 0.6 parts, 0.8 parts, 1.0 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, etc.
[0051] Preferably, the weight portion of the auxiliary cross-linking agent is 0.3-1 part, for example, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, etc.
[0052] Preferably, the weight portion of the ultraviolet light stabilizer is 0.1-1 part, for example, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, etc.
[0053] Preferably, the weight proportion of the ultraviolet light absorber is 0-1 part, for example, 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, etc.
[0054] Preferably, the weight portion of the lubricant is 0.5-1 part, such as 0.6 part, 0.7 part, 0.8 part, 0.9 part, etc.
[0055] Preferably, the weight proportion of the silane coupling agent is 0.1-2 parts, for example, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1.0 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, etc.
[0056] As a preferred technical solution, the HJT special packaging film includes the following components in parts by weight:
[0057]
[0058]
[0059] The functional auxiliary agent includes any one or a combination of at least two of acrylic acid ester polymers and derivatives thereof containing functional groups;
[0060] The functional additive participates in the cross-linking reaction, and its molecular chain forms a cross-linked network structure with the matrix resin;
[0061] The functional group includes any one of a phosphorus-containing group, an amino group or a carboxyl group, or a combination of at least two of them.
[0062] In a second aspect, the present invention provides a method for preparing the HJT-specific encapsulation film according to the first aspect, the preparation method comprising the following steps:
[0063] The base resin and the functional additive are mixed and processed to obtain the HJT special packaging film.
[0064] Preferably, the preparation method specifically comprises the following steps:
[0065] The base resin, functional additives and silane coupling agent are mixed, melt-sheared to obtain a modified masterbatch, and then the modified masterbatch is mixed with an initiator, a co-crosslinking agent, an ultraviolet light stabilizer, an ultraviolet light absorber, and a lubricant. The mixture is then melt-extruded, cast, stretched and rolled to obtain the HJT special packaging film.
[0066] In a third aspect, the present invention provides a HJT battery, the HJT battery comprising a battery cell and the encapsulation film according to the first aspect;
[0067] The HJT cell is an amorphous silicon / crystal heterojunction solar cell with an intrinsic thin layer, and the conductive oxide film deposited on the surface of the HJT cell includes indium tin oxide.
[0068] Compared with the prior art, the present invention has the following beneficial effects:
[0069] (1) The encapsulation film of the present invention is in surface-to-surface contact with the HJT cell. The encapsulation film has high bonding strength with the HJT cell and has excellent resistance to ultraviolet light and moisture-heat aging, thereby ensuring a long service life and low light conversion efficiency attenuation rate of the photovoltaic module.
[0070] (2) The peel strength between the encapsulation film of the present invention and glass is above 202.2 N / cm, and the peel strength between the encapsulation film and HJT cell is above 91.6 N / cm. After QUV composite aging, there is no delamination, no corrosion, and no yellowing. After QUV composite aging, the peel strength retention rate between the encapsulation film and the cell is above 90.1%. After UV accelerated aging, there is no delamination or yellowing in appearance. After wet heat aging, there is no delamination or corrosion in appearance.
[0071] (3) The encapsulation film of the present invention has excellent adhesion to the battery cell, and after the reliability test of the manufactured component, the component power attenuation is low. Specifically, the attenuation rate of DH2000 is within 0.80%, the attenuation rate of UV200 is within 0.95%, the attenuation rate of TC200 is within 0.76%, the attenuation rate of HF10 is within 0.88%, and the attenuation rate of PID192 is within 0.49%. DETAILED DESCRIPTION
[0072] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0073] Example 1
[0074] This embodiment provides a packaging film, which is composed of the following components in parts by weight:
[0075]
[0076]
[0077] The mass proportion of the vinyl acetate structural unit of the EVA resin is 33%, and the melt index is 28g / 10min;
[0078] The method for preparing the packaging film comprises the following steps:
[0079] The base resin, functional additives and silane coupling agent are mixed, melt-sheared to obtain a modified masterbatch, and then the modified masterbatch is mixed with an initiator, a co-crosslinking agent, an ultraviolet light stabilizer, an ultraviolet light absorber and a lubricant for 2 hours, and then the mixture is melt-extruded, cast, stretched and rolled to obtain the encapsulation film.
[0080] Example 2
[0081] This embodiment provides a packaging film, which is composed of the following components in parts by weight:
[0082]
[0083] The mass proportion of the vinyl acetate structural unit of the EVA resin is 33%, and the melt index is 25g / 10min;
[0084] The method for preparing the packaging film comprises the following steps:
[0085] The base resin, functional additives and silane coupling agent are mixed, melt-sheared to obtain a modified masterbatch, and then the modified masterbatch is mixed with an initiator, a co-crosslinking agent, an ultraviolet light stabilizer, an ultraviolet light absorber and a lubricant for 2 hours, and then the mixture is melt-extruded, cast, stretched and rolled to obtain the encapsulation film.
[0086] Example 3
[0087] This embodiment provides a packaging film, which is composed of the following components in parts by weight:
[0088]
[0089] The POE resin melt index is 15g / 10min;
[0090] The method for preparing the packaging film comprises the following steps:
[0091] The base resin, functional additives and silane coupling agent are mixed, melt-sheared to obtain a modified masterbatch, and then the modified masterbatch is mixed with an initiator, a co-crosslinking agent, an ultraviolet light stabilizer, an ultraviolet light absorber and a lubricant for 2 hours, and then the mixture is melt-extruded, cast, stretched and rolled to obtain the encapsulation film.
[0092] Embodiment 4-7
[0093] The difference between Examples 4-7 and Example 1 is that the weight parts of the functional additives are 0.1 parts (Example 4), 10 parts (Example 5), 0.05 parts (Example 6) and 12 parts (Example 7), respectively, and the rest are the same as Example 1.
[0094] Comparative Example 1
[0095] The difference between this comparative example and Example 1 is that the encapsulation film does not include a functional auxiliary agent, and the rest is the same as Example 1.
[0096] Performance Testing
[0097] The encapsulation films described in Examples 1-7 and Comparative Example 1 were tested as follows:
[0098] (1) Peel strength with glass: According to the common test method for peel strength, the encapsulation film and the glass are partially isolated with a non-stick material, and the preformed parts are placed in a laminator at 145°C and laminated for 17 minutes for cross-linking treatment. After the laminated samples are cooled for 2 hours, the peel strength between the film and the glass is tested;
[0099] (2) Peel strength with HJT cell: According to the common test method for peel strength, the encapsulation film and the front of the cell are partially isolated with a non-stick material, and the preformed parts are placed in a laminator at 145°C and laminated for 17 minutes for cross-linking treatment. After the laminated samples are cooled for 2 hours, the peel strength between the film and the cell is tested;
[0100] (3) Performance after QUV composite aging: Same as test (2), the laminated and cross-linked sample is placed in a QUV environmental chamber. During the test, ultraviolet light and high temperature and high humidity are performed simultaneously. The QUV program is set to UV200 / DH, that is, the ultraviolet aging is performed for 200 kwh while the environmental chamber is set to high temperature and high humidity (ambient temperature 85°C, relative humidity 85%). After QUV composite aging, check the appearance of the test piece for abnormal phenomena such as delamination, corrosion, and yellowing. In addition, test the bonding performance of the cell and the film after composite aging, and calculate the peel strength retention rate with the HJT cell:
[0101] (4) UV accelerated aging performance: The sample is exposed to UV light and after 320 kwh, the HJT battery and film test pieces are observed for abnormal phenomena such as delamination, corrosion, and yellowing;
[0102] (5) Damp-heat aging performance: After maintaining the temperature at 85°C and the relative humidity at 85% for 2000 hours, observe whether the HJT battery and the film test piece have abnormal phenomena such as delamination, corrosion, and yellowing;
[0103] The test results are summarized in Table 1.
[0104] Table 1
[0105]
[0106] Analysis of the data in Table 1 shows that the peel strength between the encapsulation film of the present invention and glass is above 202.2N / cm, and the peel strength between the encapsulation film and HJT cell is above 91.6N / cm. There is no delamination, corrosion, or yellowing after QUV composite aging. The retention rate of the peel strength between the encapsulation film and the cell after QUV composite aging is above 90.1%. There is no delamination or yellowing in appearance after UV accelerated aging, and no delamination or corrosion in appearance after wet heat aging. The encapsulation film of the present invention has excellent wettability, and can flow to every corner of the HJT cell in time during the film lamination process, ensuring that the encapsulation film and the cell are in surface contact. In addition, the encapsulation film can react with the ITO layer on the surface of the HJT cell to produce a stable chemical bond, thereby improving the bonding strength with HJT. It also has excellent resistance to UV and wet heat aging, ensuring the long service life and low light conversion efficiency attenuation rate of the photovoltaic module.
[0107] Analysis of Comparative Example 1 and Example 1 shows that the performance of Comparative Example 1 is not as good as that of Example 1, proving that the performance of the encapsulation film formed without the functional additive of the present invention is poor.
[0108] The encapsulation films described in Examples 1-7 and Comparative Example 1 were laminated and cured with other materials to form photovoltaic modules, and then the module reliability test was performed. The test method refers to the international standard IEC 61215. The reliability test content includes the power gain and loss of the module after 200kwh under ultraviolet light (UV200), the power gain and loss of the module after the module wet freeze test (HF10), the power gain and loss of the module after 2000h of the module wet heat test (DH2000), the power gain and loss of the module after the module thermal cycle test (TC200), and the power gain and loss of the module after applying a voltage of -1500V for 192h under high temperature and high humidity (PID9192).
[0109] The test results are shown in Table 2 below.
[0110] Table 2. Power attenuation test results for reliability testing
[0111] Test items DH2000 UV200 TC200 HF10 PID192 Example 1 -0.61% -0.87% -0.55% -0.75% -0.31% Example 2 -0.67% -0.85% -0.59% -0.74% -0.35% Example 3 -0.66% -0.82% -0.59% -0.75% -0.32% Example 4 -0.73% -0.90% -0.63% -0.72% -0.45% Example 5 -0.42% -0.69% -0.50% -0.64% -0.28% Example 6 -0.80% -0.95% -0.76% -0.88% -0.49% Example 7 -0.31% -0.33% -0.41% -0.55% -0.21% Comparative Example 1 -2.88% -2.73% -2.16% -1.38% -2.54%
[0112] From the analysis of Table 2, it can be seen that the encapsulation film of the present invention has excellent adhesion to the battery cell, and after the reliability test of the manufactured component, the component power attenuation is low. Specifically, the attenuation rate of DH2000 is within 0.80%, the attenuation rate of UV200 is within 0.95%, the attenuation rate of TC200 is within 0.76%, the attenuation rate of HF10 is within 0.88%, and the attenuation rate of PID192 is within 0.49%.
[0113] Analysis of Comparative Example 1 and Example 1 shows that the performance of Comparative Example 1 is not as good as that of Example 1, proving that the performance of the encapsulation film formed without the functional additive of the present invention is poor.
[0114] The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A HJT special packaging film, characterized in that: The HJT special packaging film comprises the following components in parts by weight: 100 parts of base resin Functional additives 0.1-15 parts Other additives 1-8 parts; The matrix resin includes ethylene-vinyl acetate copolymer and / or POE plastic; The functional additive is composed of a combination of di(methacryloyloxyethyl) hydrogen phosphate or 2-hydroxyethyl methacrylate phosphate and polyphosphate; The other auxiliary agents include 0.2-2 parts by weight of an initiator and 0.3-1 parts by weight of a co-crosslinking agent; The functional auxiliary agent participates in the cross-linking reaction, and its molecular chain forms a cross-linked network structure with the matrix resin.
2. The HJT-specific encapsulation film according to claim 1, characterized in that: The number average molecular weight of the functional additive is 100-5000 g / mol.
3. The HJT-specific encapsulation film according to claim 1, characterized in that: The light transmittance of the matrix resin is ≥91%.
4. The HJT-specific encapsulation film according to claim 1, characterized in that: In the ethylene-vinyl acetate copolymer, the mass proportion of the vinyl acetate structural unit is 28%-33%, and the melt index is 3-28g / 10min.
5. The HJT-specific encapsulation film according to claim 1, characterized in that: The other auxiliary agents also include any one of ultraviolet light stabilizers, lubricants or silane coupling agents, or a combination of at least two of them.
6. The HJT-specific encapsulation film according to claim 1, characterized in that: The initiator includes a peroxide initiator.
7. The HJT-specific encapsulation film according to claim 1, characterized in that: The initiator includes any one of tert-butyl peroxy-2-ethylhexanoate, dibenzoyl peroxide, di-tert-butyl peroxyisopropylbenzene, 2,5-di-tert-butyl peroxy-2,5-dimethylhexane or tert-amyl peroxy-2-ethylhexyl carbonate or a combination of at least two thereof.
8. The HJT-specific encapsulation film according to claim 1, characterized in that: The auxiliary crosslinking agent includes any one of 1,6-hexanediol diacrylate, ethoxylated trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, triallyl isocyanurate, triallyl cyanurate, ethoxylated pentaerythritol tetraacrylate, ethylene glycol diacrylate or ethylene glycol dimethacrylate, or a combination of at least two thereof.
9. The HJT-specific encapsulation film according to claim 5, characterized in that: The ultraviolet light stabilizer includes bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate and / or an ultraviolet light absorber.
10. The HJT-specific encapsulation film according to claim 9, characterized in that: The ultraviolet light absorber includes 2-hydroxy-4-n-octyloxybenzophenone.
11. The HJT-specific encapsulation film according to claim 5, characterized in that: The lubricant includes silicone masterbatch.
12. The HJT-specific encapsulation film according to claim 5, characterized in that: The silane coupling agent includes γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N -(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane or vinyltri(β-methoxyethoxy)silane, any one or a combination of at least two thereof.
13. The HJT-specific encapsulation film according to claim 5, characterized in that: The weight portion of the ultraviolet light stabilizer is 0.1-1 part.
14. The HJT-specific encapsulation film according to claim 9, characterized in that: The weight proportion of the ultraviolet light absorber is 0-1 part.
15. The HJT-specific encapsulation film according to claim 5, characterized in that: The weight portion of the lubricant is 0.5-1 part.
16. The HJT-specific encapsulation film according to claim 5, characterized in that: The weight proportion of the silane coupling agent is 0.1-2 parts.
17. A HJT photovoltaic module, characterized in that: The HJT photovoltaic module comprises a HJT cell and a packaging film according to any one of claims 1 to 16; The HJT cell is an amorphous silicon / crystal heterojunction solar cell with an intrinsic thin layer, and the conductive oxide film deposited on the surface of the HJT cell includes indium tin oxide.
Citation Information
Patent Citations
Packaging adhesive film for packaging HJT battery, preparation method of packaging adhesive film and prepared photovoltaic module
CN112980340A
High-PID-resistance composite packaging adhesive film and preparation method thereof
CN113234402A
Special packaging adhesive film for heterojunction battery and preparation method of special packaging adhesive film
CN113372827A
Sealing material sheet, and sheet for solar cell modules
JP2018087283A